ANALISIS MODEL Z-SCORE UNTUK MENILAI KINERJA KEUANGAN SERTA MEMPREDIKSI KEBANGKRUTAN (Pada Perusahaan Semen yang Terdaftar di Bursa Efek Indonesia Tahun 2012- 2016) - Hairuddin Hairuddin (Fakultas Ekonomi, 2018)
This study aims to determine how the financial performance and know the prediction of bankruptcy using the model of z-score on cement companies listed on the Indonesia Stock Exchange in 2012-2016. In doing this research the researcher uses Quantitative Descriptive research approach. Sampling technique in this research use purposive sampling. Data collection techniques in this study using the method of documentation in the form of secondary data is the financial statements of cement companies. The results showed that the prediction of bankruptcy using the Z-Score model of cement companies listed in Indonesia Stock Exchange 2012-2016 are in various healthy conditions. The financial performance of Cement companies listed in Indonesia Stock Exchange 2012-2016 shows that the performance is not maximal, as evidenced by the declining value of Z-Score from year to year.